2019
DOI: 10.1002/htj.21630
|View full text |Cite
|
Sign up to set email alerts
|

Numerical computation on Marangoni convective flow of two‐phase MHD dusty nanofluids under Brownian motion and thermophoresis effects

Abstract: dusty nanofluids, Marangoni convection, space-dependent heat source, two-phase flow, wavy surface | INTRODUCTIONThe Marangoni convection is a phenomenon, which is induced by thermocapillarity or solutocapillarity, that is, the variation of surface tension of the fluid with temperature or concentration. Surface tension is one of the fluid characteristics, which remain stable basically. However, the primary conditions affecting the surface tension of the fluid are variation in temperature and addition of chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…MHD dusty nanoliquids alongside a vertical region were numerically studied by Kalpana et al. 17 The development of nanofluids and their unique properties are of major concern for large-scale inventions.…”
Section: Introductionmentioning
confidence: 99%
“…MHD dusty nanoliquids alongside a vertical region were numerically studied by Kalpana et al. 17 The development of nanofluids and their unique properties are of major concern for large-scale inventions.…”
Section: Introductionmentioning
confidence: 99%
“…Siddiqa et al [32] numerically analyzed the natural convective flow of a dusty nanofluid driven by a wavy vertical surface. Recently, Kalpana et al [33], Mishra et al [34], Saha et al [35] and Ibrahim and Gamachu [36] explored the dusty nanofluid flow problem with different surfaces and aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The width of the thermal fluid flow was found to enhance the magnetic parameter. Very recently, Kalpana et al 21 reported the combined effect of Marangoni convection, the source of heat on dusty nanofluid over a wavy sheet, and numerically the same is analyzed.…”
Section: Introductionmentioning
confidence: 99%